Sustainable mobility: The route of tires through the circular economy model. (1st May 2021) - Araujo-Morera, Javier; Verdejo, Raquel; López-Manchado, Miguel Angel; Hernández Santana, Marianella
Highlights: The circular economy model is considered for the management of tires. The 7Rs hierarchy applies from early stages of production to post-consumption. Joint academic and industrial actions are needed for an effective tire management. A sustainable circular economy alleviates current environmental concern of tires. Abstract: Until nowadays, the concept of the 3Rs (Reduce, Reuse, Recycle) has tried to develop responsible consumption habits. Nonetheless, the rise of ecological thinking has generated the appearance of four new Rs in addition to these basic 3Rs; the currently 7Rs (Reduce, Reuse, Recycle, Redesign, Renew, Repair and Recover) which refer to the actions necessary to achieve the change towards a circular economy (CE) model. This model aims at extending the lifetime of the resources through their rational and efficient use to generate value repeatedly, reducing costs and waste. In this review, we examine the route followed by tires from the CE perspective, analyzing end-of-life strategies that aim to improve the circular flow of tire rubber materials. We discuss the most relevant studies on the "7Rs" concepts applied to tires, comparing different scientific approaches, as well as their industrial and commercial implementation. We also illustrate the drawbacks and feasibility of each of the R-hierarchy strategies. From the early stages of production to the post-consumption step, the path that tires trail within this CE model evidences the commitment and efforts towards the development of effective management schemes for achieving a real sustainable mobility.